Tunable Terahertz Absorber Based on Bulk-Dirac-Semimetal Metasurface - Yannan Jiang; Wan Xinguo; Jiao Wang; Jia Wang (IEEE Photonics Journal)
We propose a tunable terahertz (THz) absorber design that utilizes a bulk Dirac semimetal (BDS)-based metasurface. The absorber consists of a BDS film with a periodic ring slot, dielectric layer, and fully reflective gold mirror. Simulations indicate that localized surface plasmon resonance is excited within certain regions close to the ring slot, leading to dipolar plasmon resonance of periodic arrays along the polarization direction, thereby producing resonant absorption. The BDS conductivity scales linearly with the Fermi level that can be tuned by bias application, enhancing the electromagnetic-field concentration and shrinking the effective current path, thereby blue-shifting the operating frequency within an ultrawideband. The thickness of the proposed design is significantly less than the resonant wavelength; therefore, the design yields an ultrathin metasurface absorber. This paper may lead to the investigations of the tunable metasurface device based on the BDS.